Persistent dyselectrolytemia in a neonate induced by liposomal amphotericin B. A case report - Puertas Sanjuan, Adrian; Parramón-Teixidó, Carlos Javier; Hernandez-Perez, Susana; Frick, Marie Antoinette; Cabañas Poy, Maria Jose (Frontiers in Pediatrics, 2023)
Background Nephrotoxicity is the most frequent serious adverse effect associated with deoxycholate amphotericin B treatment, for this reason, in recent years it has been relegated from routine clinical practice and replaced by the new liposomal formulations that have less nephrotoxicity. Nevertheless, dyselectrolytemias are a frequent adverse effect of the use of liposomal amphotericin B that usually are resolved with the withdrawal of the drug. Case presentation We present a preterm neonate of 25 weeks gestation, with preserved renal function and most electrolytes within normal limits for gestational age except for mild hyponatremia in the first month of life. Due to an infection of the central nervous system and growth of Candida albicans, he required treatment with endovenous liposomal amphotericin B as well as intrathecal deoxycholate amphotericin B showing severe hydroelectrolyte disturbances a few days after starting treatment that persisted over time even after withdrawal of both drugs. In preterm or low birth weight newborns who present unjustified, severe and difficult to correct hydroelectrolyte disturbances despite the usual treatment, a possible tubulopathy should be considered, whether hereditary, primary or secondary to toxins or drugs. What Is New and Conclusion We present the first case reported in a neonate in whom dyselectrolithemia has been maintained over time after withdrawal of liposomal amphotericin b.